Pelatihan dan Pembuatan Hand Sanitizer dan Cara Mencuci Tangan yang Baik - Anna Permatasari Kamarudin; Khadijah Khadijah; Elisa Khairani; Erna Erna; Basyirah Basyirah; Ratnawati Ratnawati; Syarifudin Syarifudin (Communio: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Covid-19 pandemic in Indonesia has started to decline. However, maintaining health and personal hygiene is an essential thing that still needs to be maintained. One way is to maintain hand hygiene. Germs will easily stick to your hands. So that hand hygiene must be carried out correctly and thoroughly. Hand sanitizer or hand soap is expensive for some people in rural areas. Therefore, making hand sanitizers from natural ingredients is an easy way to get hand sanitizers. Besides utilizing natural materials, the waste from natural hand sanitizers does not damage the environment because they come from materials that easily decompose in nature quickly. The ingredients used are aloe vera, betel leaf, and lime. The training methods used are lectures, demonstrations, and question and answer. The understanding of the training participants was carried out using a pre-test and post-test. The implementation of the training and production of hand sanitizers was attended by teachers, Class V and VI students, and parents of students. The implementation of community service is carried out at SD 2 Kebayakan District. A total of 35 participants attended this training.